IMPROVING THE DIDACTIC FOUNDATIONS OF THE CREATION OF MODERNIZED EDUCATIONAL LITERATURE AND ELECTRONIC TEXTBOOKS ON COMPUTER SCIENCE - Mamadaliyev K. R.; Mamadaliyev K. R. (Bright Mind Publishing, 2025)
The purpose of this article improving the didactic foundations of the creation of modernized educational literature and electronic textbooks on computer science. In the study, such methods as regulatory documents, analysis of educational and methodological literature, observation, study and generalization of pedagogical experience, questionnaires, text, interviews, pedagogical experiment, mathematical and statistical processing of research results were used to achieve the goal and accomplish the tasks set. Practical results include the improvement of the educational process in higher education based on electronic textbooks, pedagogical technologies, as well as the issues of providing the necessary technological and pedagogical components at the appropriate level in the teaching of sciences were highlighted in the textbook entitled “Normative foundations of the management of the pedagogical system." The process of creating modernized textbooks and electronic textbooks in computer science for pedagogical higher educational institutions has been identified as the object of research. Only 1186 students were involved in the experimental work.
Keywords: Didactic foundations, process, components, computer science.